Sistem Layanan Self Assessment Wajib Pajak Berbasis Web Pada Bapenda Kabupaten Tanjung Jabung Barat - Wijaya, Herri Yansa; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2022)
The Regional Revenue Agency of West Tanjung Jabung Regency in managing local taxes, for now the restaurant taxpayer reporting process is still reporting taxes manually. Where: 1) Taxpayers must go to the office of Bapenda Tanjung Jabung Barat to report their taxes. 2) The length of waiting time for taxpayers at the Tanjung Jabung Barat Bapenda office and the accumulation of taxpayers if the due date is near. 3) The length of the verification, calculation and determination process by officers. 4) Taxpayers must wait for the return to process tax payments at the Bank. To solve this problem, the researcher designed a Taxpayer Self Assessment Service System with the aim of being an alternative problem solving. In the design and analysis, the researcher uses the UML method and the design design uses a prototype. From the results of the analysis and design, it produces features that are useful for taxpayers, such as 1) The system also stores employee/staff data. 2) The system also stores taxpayer data (restaurants and swiftlet nests). 3) Taxpayers can view information on when tax reporting is due. 4) Taxpayers can report from home or place of business without having to come to the Tanjung Jabung Regency Regional Revenue Agency.